2004
DOI: 10.1091/mbc.e03-06-0365
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the AP-1 Adaptor Complex in Early Steps of Phagocytosis and Macropinocytosis

Abstract: The best described function of the adaptor complex-1 (AP-1) is to participate in the budding of clathrin-coated vesicles from the trans-Golgi network and endosomes. Here, we show that AP-1 is also localized to phagocytic cups in murine macrophages as well as in Dictyostelium amoebae. AP-1 is recruited to phagosomal membranes at this early stage of phagosome formation and rapidly dissociates from maturing phagosomes. To establish the role of AP-1 in phagocytosis, we made used of Dictyostelium mutant cells (apm1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 54 publications
2
38
1
1
Order By: Relevance
“…In addition, AP-1 was found on punctate endosomal structures in the cytoplasm underneath the forming phagosome, but did not decorate the plasma membrane or the membrane of the phagosome. This is consistent with the localization of AP-1 in mammalian phagocytes as reported previously in Lefkir et al (2004) and is different from the situation in Dictyostelium, where AP-1 was found on phagosomal membranes and could be identified on purified phagosomal fractions. The pattern of accumulation we observed below phagocytosed particles in murine macrophages is very different from the pattern of VAMP3 recruitment on forming phagosomes (Bajno et al, 2000;Niedergang et al, 2003), which indicates that the AP-1-positive membranes do not fuse with the plasma membrane, whereas VAMP3-positive membranes do so (see Figure 7).…”
Section: Nature Of the Ap-1-positive Vesicles And Absence Of Clathrinsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, AP-1 was found on punctate endosomal structures in the cytoplasm underneath the forming phagosome, but did not decorate the plasma membrane or the membrane of the phagosome. This is consistent with the localization of AP-1 in mammalian phagocytes as reported previously in Lefkir et al (2004) and is different from the situation in Dictyostelium, where AP-1 was found on phagosomal membranes and could be identified on purified phagosomal fractions. The pattern of accumulation we observed below phagocytosed particles in murine macrophages is very different from the pattern of VAMP3 recruitment on forming phagosomes (Bajno et al, 2000;Niedergang et al, 2003), which indicates that the AP-1-positive membranes do not fuse with the plasma membrane, whereas VAMP3-positive membranes do so (see Figure 7).…”
Section: Nature Of the Ap-1-positive Vesicles And Absence Of Clathrinsupporting
confidence: 88%
“…These observations were made when we stained the cells with antibodies against clathrin or AP-2 or when we expressed clathrinDsRed or alpha-adaptin-GFP, which rules out a problem of detection by the antibodies used. This observation differs from some studies reporting the presence of clathrin in phagocytic cups (Aggeler and Werb, 1982;Takemura et al, 1986;Perry et al, 1999;Castellano et al, 2000;Lefkir et al, 2004). Many differences in the experimental systems might explain these discrepancies.…”
Section: Nature Of the Ap-1-positive Vesicles And Absence Of Clathrincontrasting
confidence: 70%
See 1 more Smart Citation
“…6F). phagosomal and macropinosome membranes, the specificity of protein internalization is unclear (49)(50)(51). To assess this lack of specificity, we labeled surface proteins by biotinylation and looked for their presence in purified early phagosomes.…”
Section: Wash Drives Recycling Of Surface Proteins From Early Macropimentioning
confidence: 99%
“…Differently from what is observed in Drosophila, the clearance of dying cells in C. elegans , as well as in Dictyostelium discoideum (Arnoult et al 2001), is performed by non specialized neighboring cells. Only a few reports have been made on phagocytosis of dying cells in the D. discoideum (Arnoult et al 2001), the more recent being the involvement of the adaptor complex-1 (AP-1), normally participating in the budding of clathrin-coated vesicles from the trans-Golgi network and endosomes (Lefkir et al 2003); the authors generated Dictyostelium mutant cells, disrupted for AP-1 medium chain, and found impaired phagocytosis, mainly for large particles. There are no evidences, until now, of circulating molecules important for the process of engulfment in C. elegans.…”
Section: Apoptotic Cell Recognition In Mammalian Systems: Redundancymentioning
confidence: 99%